A Simulation Tool for Hurricane Evacuation Planning. (24th February 2010) - Fonseca, Daniel J.; Moynihan, Gary P.; Johnston, Jordan; Jennings, Jordan
Abstract : Atlantic hurricanes and severe tropical storms are a serious threat for the communities in the Gulf of Mexico region. Such storms are violent and destructive. In response to these dangers, coastal evacuation may be ordered. This paper describes the development of a simulation model to analyze the movement of vehicles through I-65, a major US Interstate highway that runs north off the coastal City of Mobile, Alabama, towards the State of Tennessee, during a massive evacuation originated by a disastrous event such a hurricane. The constructed simulation platform consists of a primary and two secondary models. The primary model is based on the entry of vehicles from the 20 on-ramps to I-65. The two secondary models assist the primary model with related traffic events such as car breakdowns and accidents, traffic control measures, interarrival signaling, and unforeseen emergency incidents, among others. Statistical testing was performed on the data generated by the simulation model to indentify variation in relevant traffic variables affecting the timely flow of vehicles travelling north. The performed statistical analysis focused on the closing of alternative on-ramps throughout the Interstate.